Business Plan of biohacking laboratories : BioFit - Bachukin, Dmitrii (2019)
The main purpose of writing the work is to write a business plan with further implementation in real life. The business plan consists of theoretical and practical parts. This paper will mention the definition of biohacking, as well as applied analyses to assess the potential of the enterprise. Also, were performed the analyses of the market of the Czech Republic in the sphere of healthy lifestyle of the population both on the Internet and with the use of the questionnaire is carried out. In addition, the marketing strategy of the enterprise was investigated, and the financial plan was implemented. In the end, it was concluded that the company is has the potential to become a successful.